Ribociclib for post-menopausal women with HR+/HER2- advanced or metastatic breast cancer. Issue 11 (2nd November 2017) - Zangardi, Mark L.; Spring, Laura M.; Blouin, Gayle C.; Bardia, Aditya
ABSTRACT: Introduction : The introduction of CDK4/6 inhibitors, such as ribociclib, has changed the treatment landscape for post-menopausal women with HR+/HER2- advanced or metastatic breast cancer. As first-line treatment of HR+/HER2- MBC, the addition of a CDK4/6 inhibitor to an aromatase inhibitor improves progression-free survival compared to an aromatase inhibitor alone. Areas covered : In this drug profile, we review the current market for HR+/HER2- MBC, as well as the characteristics, mechanism, pharmacology, pharmacodynamics, pharmacokinetics, metabolism, clinical efficacy, toxicities, monitoring, and dosing modification of the CDK4/6 inhibitor ribociclib. Expert commentary : CDK4/6 inhibitors, such as ribociclib, improve outcomes in post-menopausal women with HR+/HER2- MBC. The most common toxicity of ribociclib is neutropenia, which is generally not complicated and can be managed with dose modification and/or supportive care measures. Additional research will help better define the optimal clinical use of ribociclib.